On convection phenomena during high pressure treatment of liquid media - Kowalczyk, Wojciech; Delgado, Antonio (High Pressure Research, 2007)
In the current contribution, investigations of the high hydrostatic pressure process up to 400MPa and temperatures up to 353K are carried out by means of dimensional analysis. The thermofluiddynamical mechanisms are analysed for three different sizes of a high pressure chamber, two different pressure generation systems and two model-fluids that differ in viscosity. Forced convection during compression/decompression and free convection during constant pressure phase are considered separately. The results contain process parameter study based on dimensionless numbers derived from conservation equations of mass, momentum and energy. Either dimensionless process parameters or the fluid dynamical and thermodynamical time scales are presented as a function of pressure and temperature. Relations according to heat transfer and fluid flow mechanisms during high pressure treatment are discussed.
UnivIS-Import:2015-03-09:Pub.2007.tech.ITC.stmmec.onconv
Keywords: Convection; Dimensional analysis; Fluid dynamics; High hydrostatic pressure; Thermodynamics